Chapter The economic-environmental impact analysis in the choice of the management of the dredging materials od a port basin in relation to the classification and the quality of the same: the experience of the port of Termoli (2018) - Cioffi, Antonietta (Proceedings e report, 2020)
The work to be illustrated shows the comparison of the economic and environmental impact analysis in astudy case: "Dredging work on the seabed of the port of Termoli 2018". The entry into force of Ministerial Decree 173/2016 (ecotoxicological characterization of the sediments of the dredging area and of the diving area led). The new assessment required the search for solutions that summarized the economic aspects, linked to the financing available, and the adoption of a new technology that would allow a system process aimed at a better environmental protection.